CRIMINOLOGICAL STUDY ON THE CRIME OF CHILD ABUSE IN TERNATE CITY (CASE STUDY 2019 - 2021) - Fahria Fahria; Muh Mufti M Djafar (Universitas Muhammadiyah Mataram, 2022)
This study aims (1) to find out what factors are causing the occurrence of criminal acts of child abuse in Ternate City. (2) what are the efforts to overcome the occurrence of criminal acts of child abuse. This research was conducted in the jurisdiction of the City of Ternateto be precise at the South Ternate City Sector Police Office and the North Maluku NGO Daulat Perempuan (Daur Mala) office. The type of research used is empirical, namely research using an approach model by looking at the legal reality in society. In this study, the authors conducted interviews with the Satlantas Sector of Ternate City and also made direct observations in the field of this research using qualitative and quantitative analysis techniques.The author obtained data by conducting direct interviews by taking data directly from the South Ternate City Sector Police Office and the North Maluku Daulat Perempuan NGO office (Daur Mala) and taking data from the relevant literature, namely literature, books and legislation relating to the problem. The results of the research that have been carried out, it is concluded that (1) That the factors that cause child abuse, the main cause is economic factors, this cause is the main driving force for parents to abuse children and cultural factors of the people of Ternate City who have a strong character. hard at dealing with a problem.